Founder Management and Innovation: An Empirical Analysis Based on the Theory of Planned Behavior and Fuzzy-Set Qualitative Comparative Analysis - Ma, Chun-Ai; Xiao, Rong; Chang, Heng-Yu; Song, Guang-Rui (Frontiers in Psychology, 2022)
Based on the expanded theory of planned behavior, this paper first explores the configuration relationship between founder management and innovation by using the fuzzy- set qualitative comparative analysis (fsQCA). Based on the theory of planned behavior, this paper divides the behavior intention of founders into three categories: attitude, subjective norm and perceived behavior control. Using fsQCA, we found that there are two ways to achieve high innovation input of enterprises. In combination with the two ways, the factors such as a founder is male, highly educated and large scale of firms can effectively increase the innovation input of firms, which is consistent with the three aspects of the behavioral intention of the theory of planned behavior, it proves that the theory of planned behavior can effectively explain the configuration relation between the founder and firm innovation. In addition, this paper finds that the innovation output is different from the innovation input, it depends on the innovation ability of the firm itself, and is little influenced by the external environment.